Perceptions about exposure to pesticides among rural school students: identified controversies - Simone Domingues Garcia; Dulce Maria Strieder (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify, according to students' perception, controversies related to the term "pesticide" and its influence on health. Methods: field research, with qualitative analysis via discursive textual analysis. Collective interviews were carried out with students of ninth grade of elementary school from four rural schools in the western region of Paraná. Results: when analyzing students' statements, it was identified that pesticides are part of their reality and that of the local community Controversies related to pesticides and health arose, with emphasis on the form of production and the understanding of the real harm generated by exposure and use of pesticides. Conclusions: approaching pesticides in the context of education and health is essential so that there is a strengthening of discussions, in a critical and contextualized way, in school spaces, expanding the look at the topic as a way of enriching understandings and discourses on the subject.